Pengaruh Lokasi, Harga, dan Promosi terhadap Keputusan Penggunaan Layanan Jasa Wafi Laundry di Kota Bengkulu - Pulungan, Guntur Alamsya Putra; Armi, Muhammad Noor; Waliamin, Janusi (Jurnal Manajemen Bisnis dan Keuangan, 2024)
The purpose of this study was to determine whether there was an influence of location, price, and promotion on the decision to use Wafi Laundry services in Bengkulu City. The method used in this study was distributing questionnaires. This study is a quantitative approach study. The population of the study was Wafi Laundry customers, 160 samples were selected to represent Wafi Laundry customers. The analysis tool used in this study used SPSS 22. The data analysis method used was multiple linear regression. The results of the study showed that: 1) location did not have a significant effect on the decision to use Wafi Laundry services; 2) price had a significant effect on the decision to use Wafi Laundry services; 3) promotion had a significant effect on the decision to use Wafi Laundry services; and 4) location, price, and promotion had a simultaneous effect on the decision to use Wafi Laundry services.